(untitled) (Mustansiria Dental Journal, 2018)
Alveolar bony defects represent one of the most common problems that face oral surgeons who practice dental implant placement. This case report describes a modification of a recent technique that aims to restore a bony defect in the implant site using a cylindrical bone block autograft taken from the patient’s own chin; then to make both clinical and radiographic evaluation of the prognosis periodically over six months postoperatively. The technique was found to be effective and successful as a treatment option to restore implant site bony defects.